HUBUNGAN GANGGUAN GIZI ANAK BALITA BERDASARKAN INDEKS ANTROPOMETRI TUNGGAL DAN KOMBINASI DENGAN MORBIDITAS DAN IMPLIKASINYA - Yekti Widodo; Sri Mulyati; Heryudarini Harahap (Persagi, 2010)
Background: Under weight, stunting and wasting are single anthropometry index that are not enough to predict prevalence of under nutrition. Using underweight as indicator to calculate prevalence of under nutrition can be under estimate or over estimate because of underweight is the result of stunting and wasting, not because of the sum of stunting and wasting. Objectives: The aim of this data analysis was to compare the relationship of prevalence of children under five under nutrition with morbidity between single and composite indices. Methods: The source of data from Health Research Basic (Riset Kesehatan Dasar) 2007/2008. Under five year nutritional status was analysis with WHO Anthro 2009 software. The statistically analysis conducted with X2 statistical test. Results: The prevalence of severe malnutrition (z-score <-3 SD, WH0-2005) based on single anthropometry index for underweight (weight/age) was 4.8%, stunting (height/age) was 18.8%, and wasting (weight/height) was 6.2%, however based on combination indices, the prevalence of severe malnutrition was 25.5%. The severe and moderate malnutrition (z-score <-2 SD, WH0-2005) based on single anthropometry indices was 19.0%, stunting was 37.0%, and wasting was 14.4%, whereas based on combination indeces the prevalence of severe malnutrition and mild malnutrition was 50.1%. The risk of upper respiratory infection, diarrhea, and measles was higher (odd ratio: 1.1- 1.4) on children with combination indices than single anthropometry indices. Conclusions: Composite anthropometry analyses could explain under five children that severely and totally malnourished. Based on combination indices one out of four under five children was severely malnourished and one out of two children was malnutrition. The morbidity was higher on children with composite indices than single anthropometry indices. Keywords: composite indices, anthropometry, severe-malnourished prevalence